Studying Indonesian Local Streaming Services Adoption Using Extended UTAUT2 Model - Santoso, Muhammad Dimas Arief; Ramantoko, Gadang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the factors that influence continue use intention among local streaming service users from Indonesia namely Vidio using UTAUT2 model and additional variables in the form of Discovery of New Content and Ubiquity. This research using 401 Vidio user respondents and analyzing using SmartPLS software. The results of this study shows performance expectancy, social influence, price value, habit, and ubiquity are considered to significantly influence the continuance intention for the Indonesian local streaming services named Vidio. This study is the first ever to examine the adoption of local OTT streaming services in the country of Indonesia using the extended UTAUT2 model.